2020
DOI: 10.1021/acs.jcim.0c00929
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Reveals a DNA-Induced Dynamic Switch Triggering Activation of CRISPR-Cas12a

Abstract: CRISPR-Cas12a is a genome-editing system, recently also harnessed for nucleic acid detection, which is promising for the diagnosis of the SARS-CoV-2 coronavirus through the DETECTR technology. Here, a collective ensemble of multimicrosecond molecular dynamics characterizes the key dynamic determinants allowing nucleic acid processing in CRISPR-Cas12a. We show that DNA binding induces a switch in the conformational dynamics of Cas12a, which results in the activation of the peripheral REC2 and Nuc domains to ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 58 publications
7
50
0
Order By: Relevance
“…This indicates that the distance between WED and Nuc domain and the WED domain and REC lobe do not significantly change when Cas12a progresses through its activity cycle. This is in agreement with structural studies ( 2 , 21 ) and molecular dynamics simulations ( 50 ), in which only marginal changes in distances between these positions can be detected ( Supplementary Figure S7 ). Using the Cas12a Nuc-REC variant, a low FRET population with a FRET efficiency of 0.12 (± 0.04) and a high FRET population ( E = 0.97 ± 0.01) can be detected for the nucleic-acid free Cas12a.…”
Section: Resultssupporting
confidence: 91%
“…This indicates that the distance between WED and Nuc domain and the WED domain and REC lobe do not significantly change when Cas12a progresses through its activity cycle. This is in agreement with structural studies ( 2 , 21 ) and molecular dynamics simulations ( 50 ), in which only marginal changes in distances between these positions can be detected ( Supplementary Figure S7 ). Using the Cas12a Nuc-REC variant, a low FRET population with a FRET efficiency of 0.12 (± 0.04) and a high FRET population ( E = 0.97 ± 0.01) can be detected for the nucleic-acid free Cas12a.…”
Section: Resultssupporting
confidence: 91%
“…This is in agreement with structural data for FnCas12a and AsCas12a (2,17,3638, 20,21,3035). Our finding that the ternary complex is more flexible than the binary complex agrees with recent molecular dynamics simulations that showed the increased flexibility of the REC and Nuc lobe in the ternary complex (43). We found that loading of the DNA target is more efficient when a ssDNA target is provided suggesting that the formation of a Cas12a-crRNA-dsDNA complex is energetically demanding.…”
Section: Discussionsupporting
confidence: 91%
“…This indicates that the distance between WED and Nuc domain and the WED domain and REC lobe do not significantly change when Cas12a progresses through its activity cycle. This is in agreement with structural studies (2, 21) and molecular dynamics simulations (43), in which only marginal changes in distances between these positions can be detected ( Figure S7). Using the Cas12a Nuc-REC variant, a low FRET population with a FRET efficiency of 0.12 (± 0.04) and a high FRET population (E = 0.97 ± 0.01) can be detected for the nucleicacid free Cas12a.…”
Section: Cas12a Adopts Three Conformational States During Its Activitsupporting
confidence: 93%
“…A similar allosteric control orchestrating interdependent domain dynamics was also identified in the activation of yet another CRISPR‐Cas system, viz. Cas12a, upon binding with the target dsDNA 65 . An allosteric regulation was also found to occur upon initial PAM recognition, governing the conformational mobility of the catalytic HNH domain 16,17 .…”
Section: Discussionmentioning
confidence: 96%
“…Cas12a, upon binding with the target dsDNA. 65 An allosteric regulation was also found to occur upon initial PAM recognition, governing the conformational mobility of the catalytic HNH domain. 16,17 Specifically, the recognition lobe was found to exert an allosteric control of the HNH activation through the REC2 and REC3 regions.…”
Section: Discussionmentioning
confidence: 98%